2018
DOI: 10.1145/3161186
|View full text |Cite
|
Sign up to set email alerts
|

CoCo

Abstract: We present and discuss a fully-automated collaboration system, CoCo, that allows multiple participants to video chat and receive feedback through custom video conferencing software. After a conferencing session, a virtual feedback assistant provides insights on the conversation to participants. CoCo automatically pulls audial and visual data during conversations and analyzes the extracted streams for affective features, including smiles, engagement, attention, as well as speech overlap and turn-taking. We vali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 39 publications
(10 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The authors showed that mood self-tracking improves cohesion within teams, and leads managers to react proactively to changes in team members' moods (Rivera-Pelayo et al, 2017). Samrose et al (2017) also showed that providing teammates with post-session feedback on the group dynamics (including emotions) changes the way they participate.…”
Section: Emotion Awareness and Tutors' Feedback To Learnersmentioning
confidence: 98%
“…The authors showed that mood self-tracking improves cohesion within teams, and leads managers to react proactively to changes in team members' moods (Rivera-Pelayo et al, 2017). Samrose et al (2017) also showed that providing teammates with post-session feedback on the group dynamics (including emotions) changes the way they participate.…”
Section: Emotion Awareness and Tutors' Feedback To Learnersmentioning
confidence: 98%
“…(2) Enhance awareness of the least talkative person: Related work has shown that gaze, head, and body orientation are helpful social cues for managing turn-taking in multiparty conversation (Duncan, 1972;Kuzuoka et al, 2010). Furthermore, previous work has shown that visualizing every attendant's participation enhanced equal participation (Samrose et al, 2018). Based on these related works, we implemented the virtual moderator to orient its head and body toward the least talkative person to engage them in the discussion by encouraging them to take turns or reminding others to include them in the debate (Figure 1).…”
Section: Related Workmentioning
confidence: 99%
“…Samrose and colleagues evaluated ways of analyzing and visualizing online video communication [12]. As early as 2003, Anne Massey analyzed and visualized temporal patterns in global virtual project teams to explore "the nature of team interaction and the role of temporal coordination in asynchronously communicating GVPTs" [13].…”
Section: Related Workmentioning
confidence: 99%